2013
DOI: 10.1371/journal.pone.0072358
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 or USF2 Contributes to HIF Target Gene Specificity

Abstract: The HIF1- and HIF2-mediated transcriptional responses play critical roles in solid tumor progression. Despite significant similarities, including their binding to promoters of both HIF1 and HIF2 target genes, HIF1 and HIF2 proteins activate unique subsets of target genes under hypoxia. The mechanism for HIF target gene specificity has remained unclear. Using siRNA or inhibitor, we previously reported that STAT3 or USF2 is specifically required for activation of endogenous HIF1 or HIF2 target genes. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Although no previous connection with STAT3 signaling has been made, p70S6K is known to up-regulate hypoxia inducible factor 1 α (HIF1α) protein expression, a known STAT3 binding partner, associated with increased angiogenesis and metastatic capacity (27)(28)(29). In breast cancer cells specifically, it has been shown that both STAT3 phosphorylation and HIF1α expression are required for the optimal transcription of a wide array of cancer-promoting factors, as these proteins bind cooperatively at many genomic loci (29). Through the synergistic activation of these distinct targets, STAT3 may be more optimally able to initiate transcription of metastasis and survival-promoting proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although no previous connection with STAT3 signaling has been made, p70S6K is known to up-regulate hypoxia inducible factor 1 α (HIF1α) protein expression, a known STAT3 binding partner, associated with increased angiogenesis and metastatic capacity (27)(28)(29). In breast cancer cells specifically, it has been shown that both STAT3 phosphorylation and HIF1α expression are required for the optimal transcription of a wide array of cancer-promoting factors, as these proteins bind cooperatively at many genomic loci (29). Through the synergistic activation of these distinct targets, STAT3 may be more optimally able to initiate transcription of metastasis and survival-promoting proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest, moreover, that USF2 is required for induction of HIF2α responsive genes (including PAI-1) under hypoxic conditions likely involving recruitment of the histone acetylases p300 and CBP [Palmeri et al, 2002]. While introduction of a USF2 expression vector alone stimulated PAI-1 promoter activity, co-transfection of a construct encoding a stabilized form of HIF2α along with the USF2 vector potentiated PAI-1 transcription more than either alone [Pawlus et al, 2013]. …”
Section: Discussionmentioning
confidence: 99%
“…Multiple signaling networks influence USF1/2 function largely through site-specific phosphorylation; dimer composition and recruited co-factors dictate target gene expression and growth control [Pawlus et al, 2013; Qi et al, 2006; Gailbert et al, 2001]. The cell cycle-related anti-proliferative functions of USF1/2, moreover, are context-dependent and involve specific mitogen-activated (p38, PKC, PKA) and cyclin-dependent (CDK1, CDK4) kinases as well as the APC, p27, BRCA2, p53 and TGF-β1 tumor suppressor pathways [Corre and Gailbert, 2005; Luo and Sawadogo, 1996; Jaiswal and Naravan, 2001; Qyang et al, 1999; Kim et al, 2008; Jung et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The CA9 and PAI1 promoters were cloned from CA9P/Luc and PAI1P/Luc (18, 19) using Advantage GC cDNA polymerase (Clontech) and then inserted into the pcDNA3.1 plasmid, replacing the CMV promoter. 2 copies of HRE (hypoxia response element/HIF binding sites) from the PAI1 promoter were added upstream of SV40 minimal promoter in the pGL3/Luc vector to produced the 2HRE/Luc construct, from which the 2HRE/SV40 was PCR amplified and replaced the CMV promoter in the pcDNA3.1 vector.…”
Section: Methodsmentioning
confidence: 99%